Shaping Urban Futures in Mongolia : Ulaanbaatar, Dynamic Ownership and Economic Flux - Plueckhahn, Rebekah (Book collections on Project MUSE., 2020)
Shaping Urban Futures in Mongolia discusses the lived experience of urban development, redevelopment and change in Ulaanbaatar, Mongolia.